EDUKASI MASYARAKAT TERKAIT HAK WARIS ANAK ANGKAT MENURUT HUKUM ADAT (Studi Kasus di Desa Sumberklidung Kecamatan Tegalsiwalan Kabupaten Probolinggo) - Edy Sumarno,; Wawan Susilo,; Nando Dwi Kurniawan, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
In accordance with the nature of life, we as humans at certain times need each other as fellow creatures of God. This is why we are united in marriage. Children are a mandate given by God Almighty to husband and wife to be raised and educated so that they can live independently and bring happiness to their parents. Children are also expected to protect the interests and care for their mother and father in old age. Therefore, the importance of children in a family and society is still considered incomplete without children.Therefore, when a family, tribe, or clan faces the reality of not having children, the family, tribe, or clan generally adopts a child to prevent the extinction of themselves or the next generation. In customary inheritance law, children hold a crucial position as successors to their parents' assets, while the purpose of marriage according to customary law is solely to produce children or continue the lineage. As stated by R. Soepomo (1993:79), the purpose of marriage in relation to inheritance law is:"The purpose of marriage according to traditional Indonesian understanding is to continue the lineage and descendants. Therefore, parental assets must be provided as successors. If a husband and wife have children, the purpose of marriage has been achieved. According to Javanese customary law, basically, both sons and daughters born later, regardless of religion, have the same rights to inheritance from their parents. This equal right means that adopted children have the right to receive equal treatment from their parents in the process of inheriting their inheritance."